2015
DOI: 10.1016/j.visres.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

A statistical perspective to visual masking

Abstract: A stimulus (mask) reduces the visibility of another stimulus (target) when they are presented in close spatio-temporal vicinity of each other, a phenomenon called visual masking. Visual masking has been extensively studied to understand dynamics of information processing in the visual system. In this study, we adopted a statistical point of view, rather than a mechanistic one, to investigate how mask-related activities might influence target-related ones within the context of visual masking. We modeled the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 38 publications
6
30
2
Order By: Relevance
“…Therefore, we determined the number of trials required to reject the null hypothesis (i.e., the transformed performances with and without a mask are equal) by a two-sample t-test with a power level larger than 0.7. In a previous study, we found that the average standard deviation of transformed-performance across observers is roughly 0.15 (Agaoglu et al, 2015). We also found small-to-moderate effect sizes (defined as the difference between two conditions divided by the standard deviation of one group (Cohen, 1988)) between baseline and weak masking conditions.…”
Section: Stimuli and Proceduressupporting
confidence: 61%
See 3 more Smart Citations
“…Therefore, we determined the number of trials required to reject the null hypothesis (i.e., the transformed performances with and without a mask are equal) by a two-sample t-test with a power level larger than 0.7. In a previous study, we found that the average standard deviation of transformed-performance across observers is roughly 0.15 (Agaoglu et al, 2015). We also found small-to-moderate effect sizes (defined as the difference between two conditions divided by the standard deviation of one group (Cohen, 1988)) between baseline and weak masking conditions.…”
Section: Stimuli and Proceduressupporting
confidence: 61%
“…In sum, these findings support the aforementioned informal observations that there is no clear or consistent trend across observers in the dependence of the standard deviation parameter on SOA and set-size. In our previous work (Agaoglu et al, 2015), we found that both the standard deviation of the Gaussian and the weight of the uniform distribution in the GU model correlated with the metacontrast function. The correlation of the weight parameter was higher than the correlation of the standard deviation.…”
Section: Modelingmentioning
confidence: 75%
See 2 more Smart Citations
“…We used Bayesian model comparison (BMC) technique (MacKay, 2003; Wasserman, 2000) to select the best statistical model to capture the data (for a step-by-step derivation of this technique, see Agaoglu, Agaoglu, Breitmeyer, & Ogmen, 2015, or Ester et al, 2015). In short, this technique computes the likelihood of data given a certain model, penalizes models with more free parameters, and assigns proportionately more weight to the penalizing factor for larger data sets in estimating the model performance.…”
Section: Methodsmentioning
confidence: 99%